Twitter Sentiment Analysis on Green Finance - Syahdatul Maulida; Bashir Ammar Hakim (Accounting and Sustainability, 2022)
This research aims to analyze public sentiment regarding the development of green finance worldwide using primary data extracted from Twitter tweets. The research methodology employed is a qualitative approach with the utilization of Python Library software known as VADER (Valence Aware Dictionary and Sentiment Reasoner) to classify sentiments within these tweets. The findings of this study indicate that the majority of the public holds a positive sentiment of 60.2% towards green finance, followed by a neutral sentiment at 26.7%, and a negative sentiment at 13.1%. Some frequently mentioned keywords in the tweets include green finance, finance minister, sustainable finance, green energy, and green bond. The objective of this research is to provide a comprehensive overview of public perceptions of green finance, encompassing its positive aspects, advantages, potentials, and benefits, while also identifying potential weaknesses and threats associated with negative perceptions of green finance. With a better understanding of public sentiment, it is hoped that relevant stakeholders can take appropriate actions to strengthen the green finance ecosystem and raise awareness and support for sustainable finance.